ANALYSIS OF GRABAG GUIDE APPLICATION ACCEPTANCE FOR INTRODUCTION TO TOURIST ATTRACTIONS USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Setiya Putra, Yusuf Wahyu; Machmudi, Moch Ali; Naim, Abdul Ghani (Jurnal Teknik Informatika (Jutif), 2024)
This research aims to analyze application user acceptance of the tourism introduction Android application in Grabag District, Magelang Regency using three (3) variables contained in the TAM (Technology Acceptance Model) model, namely Attitude towards Use, Perception of Ease of Use and Perception of Usefulness. This research needs to be carried out to resolve the problem of application acceptance which has an impact on the level of tourist visits, so that later application development and improvements can be carried out according to needs. The respondents used were 81 users consisting of sub-district officers, business or tourism owners and tourists. To obtain data whose validity and reliability have been tested and then analyzed using multiple linear regression techniques, a data collection method using a questionnaire was used. The results of the analysis of the 1st regression equation show that the Perception of Usefulness variable (X1) has a significant influence on the Attitude towards Use variable (Y). The Perception of User Ease variable (X2) has a significant influence on the Attitude towards Use variable (Y). The results of the analysis of the 2nd regression equation show that variables X1 and X2 together have a significant influence on Attitude to Use (Y).